Evaluasi Kesesuaian Lahan Tanaman Hortikultura Berbasis Sistem Informasi Geografis di Kecamatan Busungbiu Kabupaten Buleleng - Berahmana, Firos Henriahna; Sumarniasih, Made Sri; Bhayunagiri, Ida Bagus Putu (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024)DO - 10.24843/AJoAS.2024.v14.i03.p01, 2024)
Evaluation of Land Suitability for Horticultural Plants Based on Geographical Information Systems in Busungbiu District Buleleng Regency. Horticultural crops are commodities that are of high value and have many benefits. Every year the horticultural production in Busungbiu District continues to decline, especially the types of fruits. This study aims to determine the actual and potential land suitability, limiting factors, and land use direction for several horticultural crops. The crops evaluated were durian, banana, and mangosteen. The methods used were field survey, laboratory analysis, and land suitability classification by matching the quality and characteristics of the land with the requirements for plant growth. The results show that the actual land suitability class is S1 to S3 with limiting factors including rainfall, temperature, drainage, soil depth, texture, N-total, P-available, soil pH, Base Saturation, and slope. Improvement efforts made are improving the drainage system, adding organic materials, and applying fertilizers containing P and N elements such as TSP or SP36, phonska, and urea. Commodities that are prioritized in the study area are durian and banana.